The Hydrogeological Characteristics of Thick Alluvium with High Water Level and the Influence on Zhaogu Mining Area, Henan Province, China. (27th October 2022) - Miao, Wei; Xu, Yanchun; Guo, Ying; Zhang, Ermeng; Zhuo, Yunliang; Huang, Lei; Ma, Zimin; Liang, Suyu
Abstract : In parts of North China Plain, there are several aquifers in the thick alluvium over the coal seam, which overlays a large amount of coal resources. Roof water inrush accident occurred during coal mining often caused by multiple reasons. Based on the case of roof water inrush in Zhaogu Mining Area, by hydrologic supplementary exploration of the north flank, the stratum data were obtained; combined with previous geological drilling data of the mine, the structural characteristics of five main aquifers and five main aquicludes in the alluvium of the north flank were classified. By pumping test of the No. 1 and the No. 2 supplementary exploration drill holes, the water richness of the 5th aquifer of north flank is identified as medium level. Three thin layers of gravel aquifer beneath the 5th aquifer were found in No. 1 drill hole, and the water richness of the lowest thin gravel (2.95 m thickness) was identified as medium by the followed pumping test, which reveals an important factor leading to the insufficient size of the safety pillar. The leakage self-closed aperture test on the sand soil of the 5th aquiclude clarifies that in case of fracture connection, it cannot resist water and sand crushing under high water pressure of the 5th aquifer. Based on the mechanism of high-pressure water on the working face supports, the calculation method of support resistance under high water pressure alluvial layer is put forward, and the main reason of roof support failure and water inrush is the insufficient support resistance, which leads to abnormal height caving. The methods of experiment and calculation are clarified for preventing water and sand inrush accident of working faces with the similar mining background.